KINETI-KIDS it's fun to be fit program: ANTHROPOMETRIC results (2008)
This study determined the effect of the Kineti-kids project in promoting healthy weight among the school children using anthropometry. Weight and height data were measured using standard techniques among 1,250 boys and girls in two private and two public high schools on five measurement periods for two years. Data were converted to weight-for-age z-scores, body mass index (BMI) and its corresponding classification levels. The mean z-scores and proportion of children by BMI categories were compared by the type of school and period of measurement using General Linear Model and Chi-square test, respectively. Results showed that the mean weight-for-age z-scores of boys and girls aged less than ten years from public school were significantly lower than those from the private school. The type of school affected the weight-for-age z scores, but the measurement period did not affect the weight-for-age z scores of the children. About 80% of the children were of normal weight-for-age while under- or overweight varied by type of school. The proportion of overweight from children of the public schools was more or less twice that of children in private schools. Among children over ten years of age, the mean BMI of 17.3 ± 3.75 among boys from the public school was significantly lower than the mean of 19.28 ± 4.36 in private schools. The same pattern of higher mean BMI were obtained among girls in the private schools. The percentage of underweight boys and girls in the public schools was about twice that from the private schools. Likewise, overweight boys and girls in private schools were about twice in proportion compared to those in the public schools. While significant effect on BMI was obtained from the type of school, the effect of measurement periods did not show significant changes at the end of two years. It is concluded that the program did not observe statistically significant changes in the proportion of underweight or overweight children across measurement periods. However, it is recommended that interventions of this kind that integrate nutrition education in the curriculum for school children should be further intensified, monitored and evaluated.
Keywords: Physical fitness for children